Mandibular magnetic distractor: preclinical validation. Issue 6 (July 2022) - Kadlub, N.; Dallard, J.; Kogane, N.; Galliani, Eva; Boisson, J.
Abstract: The feasibility of magnetic activation for mandibular distraction has been demonstrated previously. In this study, we developed a biocompatible device to evaluate the feasibility of distraction in cadaveric subjects and the functionality of the device in bench tests. To confirm, considering the dimension of the distractor, that the torque applied on the internal magnet would be sufficient to activate distraction osteogenesis we measured, for different distances, the transmitted torque between a magnet (internal and external). We evaluated the friction force of the device, and the resilience of the magnet to the sterilisation process. To confirm the feasibility of distraction with this device, we proceeded to cadaveric tests, and evaluated the satisfaction of four surgeons. The force applied to the moving plate was greater than 50 Newtons (N) with a friction coefficient of η = 0.2 . We determined a friction torque of 65.10 -3 N.mm in the distractor mechanism and demonstrated that sterilisation did not alter the magnet. Mandibular distraction had been successfully achieved in cadaveric trials, and surgeons were satisfied. This new device could be implanted in human subjects, for clinical assay, after approval by the regulatory agencies. The use of this fully internalised device should improve patients' comfort.